Penyelesaian Sengketa melalui Lembaga Alternatif Penyelesaian Sengketa (LAPS) pada Securities Crowdfunding di Indonesia - Suprapdi, Suprapdi (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2023)
This article discusses dispute resolution of the risks faced by parties in securities crowdfunding in Indonesia through Alternative Dispute Resolution Institutions (LAPS). Securities crowdfunding itself is a refinement of equity crowdfunding, which has been running first. This is because equity crowdfunding cannot be utilized by small and medium enterprises (SMEs) or start-up companies because both are not limited liability company (PT) legal entities and only issue stock securities. This research uses normative juridical research methods and a legal research approach. The results of research on securities crowdfunding dispute resolution in Indonesia through LAPS were conducted by BAPMI because securities crowdfunding is included in the capital market sector. Dispute resolution in securities crowdfunding can be through internal dispute resolution forums (settlements are carried out by internal organizers) or external dispute resolution (settlements can be through LAPS and litigation). Keywords: Dispute, LAPS, Securities Crowdfunding.